NALAR AYAT-AYAT POLITIK KEBANGSAAN: Studi Kritis atas Kontekstualisasi Penafsiran Gus Baha’ - Uzlifatul Laily; Abd. Rahman (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract The Qur'an's verses on national politics suggest that those in power should not be careless when fulfilling their duties. However, in reality, the principles of national politics have been replaced by power politics. As a result, community control has weakened, and power struggles have become increasingly rampant. Amidst the erosion of Qur'anic values in safeguarding the Indonesian national political system, young mufasir Gus Baha contextualises his interpretation to revive the spirit of politics based on the Indonesian nation's values. This research addresses two formulations: Firstly, how is the relevance of Gus Baha's interpretation products to the practice of Indonesian national politics? Secondly, how does Gus Baha's interpretation of national political verses contextualise? The method used is qualitative library research employing Paul Ricoeur's hermeneutic theory. The research concludes two things: firstly, amidst public disappointment with the performance of leaders in this country, Gus Baha provides a breath of fresh air by suggesting that relying on the leader for the community's welfare will not be useful. Secondly, according to Gus Baha's interpretation of the verses on national politics, a leader alone cannot provide great opportunities for the welfare of their people. Instead, it depends on a social system that breeds tolerance and sympathy among them. Keywords: Verses on national politics, contextualisation of interpretation, Gus Baha', Paul Ricoeur's Hermeneutics